'It's relentless': The impact of working primarily with high-risk offenders. (June 2016) - Phillips, Jake; Westaby, Chalen; Fowler, Andrew
This article uses empirical data to consider the impact that Transforming Rehabilitation has had on National Probation Service (NPS) probation officers in terms of the increased numbers of high-risk offenders on the caseload. It was hypothesised by the researchers that the expectation that NPS probation officers would deal with more high-risk offenders would result in additional pressure on them. While this is certainly the case for some probation officers who work in the newly created NPS, the data show nuance in terms of the effect this dramatic change has had on probation officers. The article shows that there are both benefits and disadvantages to having a caseload comprised primarily of high-risk cases. The article concludes with a brief discussion of the findings in terms of the training and resourcing needs required by those NPS probation officers who are struggling with the shift to primarily high-risk offender management.